101 team handball techniques, tactics and drills - Radu, Felicia Lidia; Abalasei, Beatrice Aurelia (London Bloomsbury, 2015)
During the last few years, handball - a modern and attractive high-speed game - has been fascinating more and more spectators and fans. 101 Team Handball provides sound practical advice for beginners and introduces advanced techniques and tactics for more experienced players. It focuses on technical and tactical aspects of the game for both defence and attacking situations, including : Handling the ball, Dribbling the ball, Passing and catching, Blocking, Shooting. It also includes a separate section dedicated to the goalkeeper and their training. Fully illustrated with step-by-step sequence photographs as well as action shots to aid understanding of this fast-paced sport, this is the essential tool for all handball players and coaches. -- Back cover
Foreword \ 1. Brief history of handball \ 2. Overview of rules \ 3. Handball techniques and skills \ 4. Tactics in Handball \ 5. The Handball goalkeeper \ 6. Other components of Handball training \ 7. Running /organising Handball events \ Glossary of terms \ Useful contacts \ Appendix 1: Referee signals
Keywords: Team handball; Team handball -- Training